Sedimentary Fe speciation and Fe isotope compositions from SONNE cruise SO241 - Scholz, Florian (Supplement to: Scholz, Florian; Schmidt, Mark; Hensen, Christian; Eroglu, Sümeyya; Geilert, Sonja; Gutjahr, Marcus; Liebetrau, Volker (2019): Shelf-to-basin iron shuttle in the Guaymas Basin, Gulf of California. Geochimica et Cosmochimica Acta, 261, 76-92, https://doi.org/10.1016/j.gca.2019.07.006, 2019)
Enrichments of highly reactive iron (Fe) (sum of Fe (oxyhydr)oxide, carbonate and sulfide minerals) in marine sediments and sedimentary rocks are commonly interpreted as an indication of anoxic conditions in the bottom water at the time of deposition. The model system for this proxy rationale is the semi-restricted Black Sea, where sediments underneath the anoxic and sulfidic (i.e., euxinic) deep-water are enriched in reactive Fe, which was mobilized from the surrounding shelf areas. To test whether such a shelf-to-basin Fe shuttle can operate in semi-restricted basins without euxinic deep water, we investigated sedimentary Fe speciation and Fe isotope compositions in sediments of the Guaymas Basin, Gulf of California.